A Politics of Recognition: The Legislation of Zakat Law in a Transition of New Order and Reform Era - Ali Murtadho Emzaed; Kamsi Kamsi; Ali Akhbar Abaib Mas Rabbani Lubis (Ulumuna, 2020)
This article discusses Islamic civilians' struggles in gaining recognition of ‘positivization’ of Zakat Law No. 38/1999 and analyzes dynamics of relations between religion and the state in Indonesia. A period of democratic transition from Suharto to B.J. Habibie (Reform era 1998) marked an entry point for a new phase of state juridical recognition to Islamic law. In this paper, the dynamics of political recognition of zakat law are elucidated from a historical-critical analysis. The findings are twofold. Firstly, the zakat law was enacted during B.J. Habibie’s administration, where waves of democratization began. Secondly, the Islamic civilians played an important role in institutionalizing zakat and providing political support for the Ministry of Religion's efforts in proposing Zakat Management Bill (RUUPZ) to the House of Representatives. The state acknowledged multicultural society by adopting their living religious law whose application does not threaten the nation's unity.